Spatio-temporal dynamics of European innovation: An exploratory approach via multivariate functional data cluster analysis - Imke Rhoden; Daniel Weller; Ann-Katrin Voit (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
We apply a functional data approach for mixture model-based multivariate innovation clustering to identify different regional innovation portfolios in Europe. Innovation concentration is considered as pattern of specialization among innovation types. We examine patent registration data and combine them with other innovation and economic data across 225 regions, 13 years and 8 patent classes. This allows us to identify innovation clusters that are supported by several innovation- and economy-related variables. We are able to form several regional clusters according to their specific innovation types. The regional innovation cluster solutions for IPC classes for 'fixed constructions' and 'mechanical engineering' are very comparable, and relatively less comparable for 'chemistry and metallurgy'. The clusters for innovations in 'physics' and 'chemistry and metallurgy' are similar; innovations in 'electricity' and 'physics' show similar temporal dynamics. For all other innovation types, the regional clustering is different and innovation concentrations in the respective regions are unique within clusters. By taking regional profiles, strengths and developments into account, options for improved efficiency of location-based regional innovation policy in order to promote tailored and efficient innovation-promoting programs can be derived. – – In diesem Beitrag wird eine multivariate Clusteranalyse im Paradigma funktionaler Daten auf Basis von Mischmodellen und Expectation Maximization genutzt, um die Diversität regionaler Innovationsportfolios und -dynamiken in Europa zu analysieren. Neben traditionellen Innovations- und Wirtschaftsdaten werden Daten zur Patentanmeldung als Indikator für Konzentration und -spezialisierung herangezogen, womit regionale Innovationscluster für 225 Regionen über 13 Jahre und 8 Patentklassen gebildet werden, deren latente Dynamiken aufgrund ihrer Subtilität in anderen multivariaten Analyseansätzen lediglich sehr schwer erfasst werden können. Hierbei zeigt sich, dass regionale Clusterlösungen für IPC-Klassen mit Überschneidungen im Anwendungsbereich stark ähneln, z. B. die IPC-Klassen "Physik" und "Chemie und Metallurgie" sowie "Feste Bauten" und "Maschinenbau". In den meisten Fällen zeigen sich jedoch sehr heterogene Clusterungen, die sich aus der starken Spezialisierung europäischer Regionen auf einzelne Innovationsarten ergeben. Daraus wird gefolgert, dass sich durch die Berücksichtigung regionaler Profile und Dynamiken Potenziale für effizientere standortbezogene Innovationspolitik ergeben, um effizientere regionale Innovationsförderung anzustoßen.
Keywords: O33; R12; C38; 330; Functional Data Analysis (FDA); innovation concentration; spatio-temporal cluster modeling; multivariate cluster analysis; European innovation; cluster algorithm